Analysis of time delay jitter of communication system on fault location of power line based on traveling wave method - Mingzhen LI; Jianming LIU; Hang WANG; Wenjun ZHOU (Dianxin kexue)
In order to study the time delay jitter of communication system on fault location of power line,a mathematical model of the delay jitter based on Poisson distribution was presented.The characteristic of the random delay jitter for single and multiple node cases were analyzed.Results show the delay jitter is remarkable when the communication load is high,and is insensitive when the communication load is low in the single node case.The total delay jitter is lower than the sum of the jitter in the queues on a path,and the position of the heavy load node in the path has a large influence on the total path jitter.The delay jitter with its influencing factors should be taken into account to perform optimal network design.